The Influence of the Principal's Transformational Leadership and Mastery of Strategic Management on Improving the Quality of Education in State Vocational Schools in Kayuagung District - Leila Adawiyah; Edi Harapan; Syaiful Eddy (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to determine the effect of principal transformational leadership and strategic management mastery on improving the quality of education. This study was conducted at State Vocational High Schools in Kayuagung District. This type of research is descriptive quantitative. The population in this study were 201 respondents and the sample in this study were 137 respondents with data collection techniques in the form of questionnaires. Data processing using SPSS version 22. Data analysis techniques used were data normality test, data linearity test, and data multicollinearity test. The results of the study showed that: 1) There is a significant influence between principal transformational leadership on improving the quality of education, 2) There is a significant flow between strategic management mastery on improving the quality of education, 3) There is a significant influence between principal transformational leadership and strategic management mastery on improving the quality of education.